(untitled) (REMUNOM, 2026)
Waterproofing processes should be applied to all types of constructions, such as urban buildings, bridges, and viaducts. However, they do not guarantee durability without continuous inspection and maintenance procedures. Bridges, in particular, should receive waterproofing applications during their construction, maintenance, or repairs. Waterproofing in these structures is not reserved only for those in cold climate countries, where de-icing is done using salts, which are major inducers of pathologies in concrete. It is also applied in hot climate countries. In Brazil, as in any part of the world, bridge or viaduct structures are susceptible to water percolation, mainly in deck slabs, expansion joints, and exposed cracks. This anomaly alone justifies waterproofing, aiming at protection against other anomalies in the concrete and reinforcement. Thus, greater structural durability is promoted, with the aim of achieving lower social costs related to structural rehabilitation works. This article aims to address waterproofing processes as necessary procedures to be applied to bridges and viaducts, both for new and rehabilitated structures, ensuring durability while saving resources.